2022
DOI: 10.3390/jcm11051383
|View full text |Cite
|
Sign up to set email alerts
|

Routine and Advanced Laboratory Tests for Hemostasis Disorders in COVID-19 Patients: A Prospective Cohort Study

Abstract: Background: Thrombosis is frequent during COVID-19 disease, and thus, identifying predictive factors of hemostasis associated with a poor prognosis is of interest. The objective was to explore coagulation disorders as early predictors of worsening critical conditions in the intensive care unit (ICU) using routine and more advanced explorations. Materials: Blood samples within 24 h of ICU admission for viscoelastic point-of-care testing, (VET), advanced laboratory tests: absolute immature platelet count (A-IPC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…Among them, the alteration of hemostatic processes may be of interest, predominantly because of the higher incidence of thrombotic events during COVID-19 disease. We previously described the alteration in the coagulation process in our cohort, with a particular role identified for immature platelets and thrombin generation assay, whereas d-dimers presented discouraging results [ 3 , 46 ]. On the other hand, clinical parameters such as the ROX index, which quantifies the severity of respiratory failure under HFNC, may predict the respiratory worsening of patients [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, the alteration of hemostatic processes may be of interest, predominantly because of the higher incidence of thrombotic events during COVID-19 disease. We previously described the alteration in the coagulation process in our cohort, with a particular role identified for immature platelets and thrombin generation assay, whereas d-dimers presented discouraging results [ 3 , 46 ]. On the other hand, clinical parameters such as the ROX index, which quantifies the severity of respiratory failure under HFNC, may predict the respiratory worsening of patients [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This cohort was described in a previous publication [ 3 ]. Briefly, patients were eligible for inclusion if they presented a “severe” condition related to a documented infection of SARS-CoV-2 (determined by polymerase chain reaction assay), defined as the need for ICU admission because of acute respiratory failure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports suggest that thrombin generation is enhanced in CAC ( 17 , 29 , 30 ), independent of heparin treatment ( 17 ). However, other studies showed no differences in thrombin generation during various stages of disease severity in SARS-CoV-2 infection, suggesting coagulation exhaustion ( 31 33 ). In this paper the results of serial thrombin generation experiments, performed in a cohort of severely COVID-19 patients, admitted to the intensive care unit (ICU) for mechanical ventilation, are presented.…”
Section: Introductionmentioning
confidence: 89%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection leading to the coronavirus disease 2019 (COVID-19) is associated with a multifactorial coagulopathy related to inflammation resulting from the cytokine storm [1] , [2] . Excessive amounts of thrombin are generated with a subsequent hypercoagulability state leading to a high prevalence of thrombotic manifestations, many with fatal outcomes [3] , [4] , [5] . This quickly led teams managing patients hospitalised with severe COVID-19 to raise the question of the informativity of initially performed innovative coagulation tests describing coagulation as a whole on key clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%